(untitled) (PETITUM, 2024)
ABSTRACT: The study aims to: 1) Analyze the application of material law in decision No. 106/Pid.Sus/2022/PN.Skg; and 2) Identify the judges’ considerations in the same decision. Findings indicate that the enforcement of Law No. 18 of 2013 on the Prevention and Eradication of Forest Damage is based on Article 83 paragraph (1) subparagraph b in conjunction with Article 12 letter e, specifically regarding the possession of timber without proper documentation. The court determined that the defendant, an individual who intentionally transported the timber, was sentenced to 1 year and 6 months of imprisonment and a fine of Rp. 500,000,000.00 (five hundred million rupiah). Failure to pay the fine would result in an additional 2 months of imprisonment. The judgment was based on witness testimony, evidence, and aggravating and mitigating factors. ABSTRAK: Penelitian ini bertujuan untuk: 1) Menganalisis penerapan hukum materiil dalam putusan No. 106/Pid.Sus/2022/PN.Skg; dan 2) Mengidentifikasi pertimbangan hakim dalam putusan tersebut. Hasil penelitian menunjukkan bahwa penerapan Undang-Undang Nomor 18 Tahun 2013 tentang Pencegahan dan Pemberantasan Kerusakan Hutan mengacu pada Pasal 83 ayat (1) subayat b juncto Pasal 12 huruf e, terkait kepemilikan kayu tanpa dokumen resmi. Hakim memutuskan bahwa terdakwa, yang memenuhi kriteria individu dan sengaja mengangkut kayu, dihukum 1 tahun 6 bulan penjara dan denda Rp. 500.000.000,00. Jika denda tidak dibayar, terdakwa akan menjalani tambahan hukuman 2 bulan kurungan. Putusan didasarkan pada keterangan saksi, alat bukti, serta faktor yang memberatkan dan meringankan terdakwa.